Universalism, diversity and norms: gratitude, healthcare and welfare chauvinism - Bradby, H.; Humphris, R.; Padilla, B. (Critical Public Health, 2020)
Access to universal healthcare is a normative expectation of citizens in European welfare states. As part of a comparative study of healthcare in diverse European neighbourhoods, we met women who described failures of the public healthcare system, together with gratitude for that system. Challenges to European welfare states of ageing populations, the retraction of resources available for healthcare, and globalised migration streams have been linked to xenophobic ‘welfarist’ attempts to restrict access to services for new arrivals and those seen as failing to contribute sufficiently. Stories of healthcare systems ’failure to treat symptoms, pain, and suffering in a timely and caring fashion came from eight women of non-European migrant back-grounds as part of a wider interview study in four European cities (Birmingham, Uppsala, Lisbon, Bremen). These accounts suggest that a normative aspect of welfare provision has been reproduced– that is, the expression of gratitude– despite inadequate services. Where welfarist attitudes to migration meet normative aspects of healthcare, suffering may be compounded by an expectation of gratitude. The regrettable unmet health-care need of the eight women whose cases are presented suggests that other marginalised healthcare users may also be under-served in apparently universal healthcare systems.